KONSTRUKSI MAKNA SELF-CONFIDENCE DALAM FILM ANIMASI ENCANTO - Fuadiyah, Layinatul; Afyatul Masruroh, Sayidah (Universitas Hasyim Asy'ari, 2024)
This research aims to uncover the meaning of the sign of self-confidence in the animated film Encanto using the semiotic approach of Roland Barthes and the theory of meaning by Wendell Johnson. The two main issues addressed are the meaning of self-confidence signs in the film and the construction of that meaning. Through a qualitative approach, an analysis is conducted on ten scenes in the film